Midazolam is metabolized by at least three different cytochrome P450 enzymes - Wandel, Christoph; Böcker, R.; Böhrer, Hubert; Browne, Angela M.; Rügheimer, E.; Martin, Eike (British journal of anaesthesia, 1994)
Distribution volumes and metabolism determine the pharmacokinetics of midazolam. Cytochrome P450 3A4 has been considered a significant enzyme in its metabolism. Using heterologously expressed cytochrome P450 enzymes, we have confirmed the additional involvement of cytochromes P450 3A3 and 3A5 in the hydroxylation of the midazolam. Whereas cytochrome P450 3A3 metabolized midazolam to the same extent as cytochrome P450 3A4, cytochrome P450 3A5 increased its metabolism by a factor of 2.7. The relationship of α- to 4-hydroxylation of midazolam was approximately 1.3 for cytochromes P450 3A3 and 3A4, and approximately 8.8 for 3A5. The primary location of cytochromes P450 3A3 and 3A4 is the liver in contrast with cytochrome P450 3A5, which occurs predominantly in the kidney. Therefore, further in vivo study is required to prove conclusively that enzymes in the kidney are involved in the metabolism of midazolam. Nitrendipine itself is metabolized by cytochrome P450 3A enzymes and this was shown to inhibit human liver microsomal hydroxylation of midazolam and preferentially a-hydroxylation by about 77%. 4-Hydroxylation was inhibited to 32% of control by nitrendipine. In contrast with inhibition of 4-hydroxylation, a-hydroxylation would appear to be competitively inhibited. These findings may be relevant to drug interactions in combined therapy.